Analysis of emissions from combusting pyrolysis products. (15th August 2020) - Schwartz, Nicholas R.; Paulsen, Alex D.; Blaise, Michael J.; Wagner, Andrew L.; Yelvington, Paul E.
Graphical abstract: Highlights: Pyrolysis is an alternative to municipal solid waste incineration. Self-powered pyrolysis can meet CO, NOX, and SO2 EPA emissions standards. Particulate matter emissions are the biggest concern for pyrolysis of waste. Pyrolysis does not need advanced air pollution control to meet EPA regulations. Abstract: Fast pyrolysis of organic wastes has the potential to reduce gaseous emissions and particulate matter compared to waste incineration. Fast pyrolysis converts organic material to a primarily liquid product (bio-oil), which can be burned more cleanly than solid wastes, while still providing heat/power. Pyrolysis reactors can operate without external power by burning pyrolysis products to generate process heat needed to dry feedstock and operate the reactor. The potential of processing organic wastes using pyrolysis was evaluated by determining the total emissions for a pine-fed, fast-pyrolysis system with on-site utilization of pyrolysis products. Emissions were measured during the operation of three different burners fueled by pyrolysis bio-oil, char, and gas. Measured emissions were compared to EPA standards for waste incinerators. Five of the EPA regulated pollutants (Cd, Pb, Hg, HCl, and dioxins/furans) were not observed during testing as they typically depend on feedstock composition (Cd, Pb, Hg, HCl) or are greatly reduced by burning liquid rather than solid fuels (dioxins/furans). Burning pyrolysis products met carbon monoxide (CO), nitrogen oxides (NOX ), and sulfur dioxide (SO2 ) emissions standards at 10.6 ppm, 16.8 ppm, and 2.3 ppm, respectively. PM emissions were measured at 60 mg/m 3, which exceeded the EPA limit of 30 mg/m 3 . However, PM emissions are reducible by using a baghouse filter and optimizing the bio-oil burner air–fuel ratio. These results demonstrated that pyrolysis can convert organic wastes while also meeting CO, NOX, SO2, and PM emission standards set by the EPA for waste incinerators without using advanced air pollution control systems.